Joker Movie Poster Advertisement: The Semiotic Analysis - Muazzomah, Ulfa (Journal of Literature, Linguistics, & Cultural Studies, 2023)
This study employed semiotics to establish connections among the elements utilized in advertising. The focus of the research was analyzing Joker poster advertisements using semiotic studies based on Pierce's theory. Pierce's Theory was employed to identify and categorize various types of signs, as well as analyze and describe their meanings. The objective of this study was to identify semiotic signs present in Joker Poster advertisements and interpret their meanings. The research design was descriptive and qualitative, involving document analysis. Each sign within the poster advertisements was identified and classified into three types: index, icon, and symbol. The meaning of each sign was then analyzed and explained using a triadic process model. The findings revealed that the advertisements contained semiotic signs in the form of symbols, icons, and indexes. There were 14 icons, 12 indexes, and 42 symbols identified. Symbols were more commonly used compared to indexes and icons, with text often serving as a symbol in the Joker posters. Additionally, the researcher observed that posters (icons) played a crucial role in providing initial direction to the meaning, followed by the language used in the advertisements.